2D Animation : Heroes on the street - Thaiphan, Rattayagon (Journal of Science and Technology Songkhla Rajabhat University, 2021)
The objectives of this research are 1) to develop a 2D animation titled “Heroes on the street”, 2) to evaluate the quality of the 2D animation, and 3) to study audience satisfaction with the 2D animation. The sample group we selected to evaluate the 2D animation was thirty undergraduate students from the faculty of Science and Technology at Nakhon Si Thammarat Rajabhat University. We specifically chose students who are interested in 2D animation. The research tools in this project consisted of 1) the 2D animation, 2) interviews with animation quality experts, and 3) questionnaires from the sample group. The results of the research were as follows: 1) the 2D animation titled “Heroes on the street” was developed to be a media to give knowledge about how to help people in an accident on the street 2) the evaluation from the experts based on the content and technicality of the animation was on average 4.34 out of 5, which is good, and 3) the assessment of the 2D animation by the aforementioned sample group from four areas: media content, technicality, audiovisual, and usefulness was on average 4.31 out of 5, which was also good. sample group from four areas: media content, technicality, audiovisual, and usefulness was on average 4.31 out of 5, which was also good.